Revealing the Efficacy of Thermostable Biosurfactant in Heavy Metal Bioremediation and Surface Treatment in Vegetables - Ravindran, Amrudha; Sajayan, Arya; Priyadharshini, Gopal Balasubramian; Selvin, Joseph; Kiran, George Seghal (Frontiers in Microbiology, 2020)
Biosurfactants are amphiphilic molecules which have wide application in food industry, medical, cosmetics and bioremediation. In this study a marine sponge associated bacteria MSI 54 was identified as biosurfactant producer which showed high emulsification and surface tension reducing property. The isolate MSI 54 was identified as Bacillus sp. and the biosurfactant was chemically characterized as lipopeptide analogue based on the spectral data including Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. The MSI 54 lipopeptide biosurfactant was an anionic molecule which showed high affinity towards cationic heavy metals including Pb, Hg, Mn and Cd. The heavy metal bioremediation efficacy of the biosurfactant was evaluated using atomic absorption spectroscopy, scanning electron microscopy- energy dispersive x-ray spectroscopy and high resolution transmission electron microscopy analyses. When MSI 54 lipopeptide biosurfactant was added to heavy metals, resulted in white co-precipitate of metal-biosurfactant complex. The heavy metal remediation efficacy of biosurfactant at a 2.0 x CMC (critical micelle concentration) showed removal of 75.5% Hg, 97.73% Pb, 89.5% Mn and 99.93% Cd respectively in the 1000 ppm of respective metal solution. The surface treatment of farm fresh cabbage, carrot and lettuce with 2.0 x CMC of lipopeptide showed effective removal of the surface heavy metal contaminants.